ADP Receptor Antagonists and Converting Enzyme Systems Reduce Platelet Deposition onto Collagen - Wagner, William R; Hubbell, Jeffrey A (Thrombosis and Haemostasis, 1992)
The effect of the ADP receptor antagonists ATP and adenosine 5’-(β, γ-methylene)triphosphate (AMP-PCP), and the ADP-utilizing enzyme systems creatine phosphokinase/creatine phosphate (CPK/CP) and pyruvate kinase/phosphoenol pyruvate (PK/PEP) on platelet deposition onto type I collagen was examined. An in vitro perfusion system was used, which allowed continuous visualization of the deposition of fluorescently labelled platelets. This system also provided well-controlled rheology, precise quantification of deposition, and allowed the use of heparinized whole human blood (3 u/ml). Heparinization at this level permits the local generation of thrombin near surface platelet aggregates. The contribution of ADP is thus studied with the combined effects of thrombin, thromboxane A2, and other aggregating agents present. Results from these studies indicate that ATP was capable of inhibiting deposition by 60% at 1 pM and 90% at 5 μM (whole blood cone.). AMP-PCP inhibited deposition in a dose dependent manner with a Ki of approximately 80 μM and a maximum inhibition of 60%. Inhibition by CPK/CP was measured at 20, 40, and 60 u/ml, with approximately 45% inhibition achieved for the latter two concentrations. PK/ PEP at 60 u/ml resulted in 70% inhibition. These results support a role for ADP in mediating platelet recruitment in thrombus growth on collagen. Previous work utilizing animal bleeding times supports this conclusion; the present study demonstrates that this role is not dependent upon endothelial or vasoconstrictive effects. Intraplatelet cAMP levels were raised with respect to controls upon exposure to ATP at 8.3 μM (p <0.025), and 15 μM (p <0.005), as well as AMP-PCP at 42-500 μM (p <0.005). Since increasing intraplatelet cAMP may affect platelet function, these results raise another possible interpretation for some of our platelet deposition data as well as that of previous experimenters. However, since ATP at 1 μM was not shown to affect intraplatelet cAMP, it is believed that at least part of the ATP-mediated inhibition was due to ADP receptor competition.